How does running technique change with running speed? A quantitative analysis based on practice-informed principal components - Daniel Debertin; Diego Jaén-Carrillo; Luis Enrique Roche Seruendo; Peter Federolf (Current Issues in Sport Science)
Introduction & Purpose